Challenges with pediatric anesthesia and intraoperative ventilation of the child in the resource‐constrained setting. Issue 2 (10th December 2021) - Ndikontar Kwinji, Raymond; Evans, Faye; Gray, Rebecca M.
Abstract: The systemic challenges in providing safe anesthesia, including safe ventilation, to children in resource‐constrained settings are many. For anesthesia providers caring for children, the lack of appropriate equipment, inadequate anesthesia workforce and deficiencies in postoperative care are especially difficult. The clinical decisions made by anesthesia providers around when and how to ventilate a child for surgery are influenced by all of these factors and can result in patient management which may vary significantly from that in a high‐resource setting. This educational review considers the intraoperative ventilation of a small child in a resource‐constrained setting and discusses specific challenges and context‐sensitive solutions.